Population pharmacokinetics and exposure–response analyses of daratumumab plus pomalidomide/dexamethasone in relapsed or refractory multiple myeloma. Issue 5 (28th December 2022) - Dosne, Anne‐Gaelle; Li, Xia; Luo, Man Melody; Nnane, Ivo; Dimopoulos, Meletios A.; Terpos, Evangelos; Sonneveld, Pieter; Kampfenkel, Tobias; Carson, Robin; Amin, Himal; Perez Ruixo, Juan; Zhou, Honghui; et al.
Abstract : Aim: A population pharmacokinetic (PPK) model was developed to characterize pharmacokinetics (PK) of subcutaneous or intravenous daratumumab administration in a new indication (i.e., combination with pomalidomide and dexamethasone [D‐Pd] in patients with relapsed or refractory multiple myeloma [RRMM]). Analyses were conducted to explore exposure–response (E‐R) relationships for efficacy and select treatment‐emergent adverse events (TEAEs). Methods: The PPK analysis included pooled data from the D‐Pd cohorts of the phase 3 APOLLO and phase 1b EQUULEUS studies. Covariates were evaluated in the PPK model. Model‐predicted exposures to daratumumab were compared between covariate subgroups of interest and used to investigate relationships between daratumumab exposure and efficacy and safety in APOLLO. Results: The PPK analysis included 1146 daratumumab PK samples from 239 patients (APOLLO, n = 140; EQUULEUS, n = 99). Observed concentration–time data of daratumumab were well described by a two‐compartment PPK model with first‐order absorption and parallel linear and nonlinear elimination pathways. Treatment with D‐Pd provided similar daratumumab PK characteristics versus historical daratumumab monotherapy. The E‐R dataset contained data from 290 APOLLO patients (D‐Pd, n = 140; Pd, n = 150). The PK–efficacy relationship of daratumumab supported improved progression‐free survival for patients in the D‐Pd group vs . the Pd group. Additionally, TEAEs did not increase with increasing PK exposure in the D‐Pd group. Conclusions: The PPK and E‐R analyses support the daratumumab subcutaneous 1800 mg dosing regimen in combination with Pd for treatment of patients with RRMM. No dose adjustment is recommended in this indication for any of the investigated factors, none of which had clinically relevant effects on daratumumab PK.